After Darwin : animals, emotions, and the mind - Richardson, Angelique, 1970- (Clio medica (Amsterdam, Netherlands) ;, 2013)
'What is emotion?' pondered the young Charles Darwin in his notebooks. How were the emotions to be placed in an evolutionary framework? And what light might they shed on human-animal continuities? These were among the questions Darwin explored in his research, assisted both by an acute sense of observation and an extraordinary capacity for fellow feeling, not only with humans but with all animal life. After Darwin: Animals, Emotions, and the Mind explores questions of mind, emotion and the moral sense which Darwin opened up through his research on the physical expression of emotions and the hu.